2011
DOI: 10.1016/j.molstruc.2010.12.013
|View full text |Cite
|
Sign up to set email alerts
|

A solid-state 199Hg NMR study of mercury halides

Abstract: Abstract:The principal elements of the 199 Hg chemical-shift (CS) tensors of the mercuric halides (HgX 2 , X = F, Cl, Br, and I) and the mercurous halides (Hg 2 X 2 , X = F and Cl) were determined from spectra of static polycrystalline powders and from magic-angle spinning (MAS) spectra. The CS tensors of both HgCl 2 and Hg 2 Cl 2 are axially symmetric (η = 0) within experimental error, differing from literature reports of η=0.12 and η=0.14, respectively. The principal elements of the axially symmetric CS tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
3
8
0
1
Order By: Relevance
“…For χ CuCl 2 = 0.33, this peak was found at −1106 ppm (relative to 1 M HgCl 2 in dmso); for χ CuCl 2 = 0.50, the peak appeared at −1140 ppm. These positions are consistent with the formation of chloromercurate(II) anions, 37 where the mercury is in the environment of four chlorine atoms. The lower field peak is assigned to [HgCl 4 ] 2− and the higher peak to [Hg 2 Cl 6 ] 2− .…”
Section: Reaction Of Copper(ii) Ionic Liquids With Mercurysupporting
confidence: 75%
“…For χ CuCl 2 = 0.33, this peak was found at −1106 ppm (relative to 1 M HgCl 2 in dmso); for χ CuCl 2 = 0.50, the peak appeared at −1140 ppm. These positions are consistent with the formation of chloromercurate(II) anions, 37 where the mercury is in the environment of four chlorine atoms. The lower field peak is assigned to [HgCl 4 ] 2− and the higher peak to [Hg 2 Cl 6 ] 2− .…”
Section: Reaction Of Copper(ii) Ionic Liquids With Mercurysupporting
confidence: 75%
“…1 H NMR spectra were referenced to the solvent residual peak (CDCl 3 , δ 7.24 ppm; CD 3 CN, δ 1.94 ppm; DMSO-d6, δ 2.50 ppm; pyridine-d5, δ 8.74 ppm). 13 C NMR spectra were referenced to the solvent residual peak (CDCl 3 , δ 77.0 ppm; DMSO-d6, δ 39.0 ppm; pyridine-d5, δ 150.4 ppm; CD 3 CN, δ 118.2 ppm). 199 Hg NMR was calibrated using 1 M HgCl 2 and 1 M HgI 2 as external standards.…”
Section: Methodsmentioning
confidence: 99%
“…199 Hg NMR was calibrated using 1 M HgCl 2 and 1 M HgI 2 as external standards. 13 [Caution! DMSO is readily absorbed through the skin.…”
Section: Methodsmentioning
confidence: 99%
“…Studies based on single crystals for X = F, Cl, Br were reported by Dorm (1970) and for X = F also by Grdenić & Djordjević (1956) and Schrö tter & Mü ller (1992). For the physical properties of mercurous halides, see: Zadokhin & Solodovnik (2004); Markov et al (2007Markov et al ( , 2010; Taylor et al (2011). For theoretical studies of the structures of mercurous halides, see: Liao & Zhang (1995); Liao & Schwarz (1997 Table 1 Selected bond lengths (Å ).…”
Section: Related Literaturementioning
confidence: 99%
“…Ces dernières années, ces composés ont fait l'objet de nombreux travaux, essentiellement pour leurs propriétés dynamiques (Zadokhin & Solodovnik, 2004), ferroélastiques (Markov et al 2007(Markov et al , 2010 et résonnances magnétiques nucléaires (NMR) (Taylor et al, 2011). La présence de liaisons Hg-Hg, qui est l'une des caractéristiques de ce type de composé a suscité plusieurs études quant à la nature et aux propriétés de ces liaisons (Liao & Zhang, 1995;Liao & Schwarz, 1997).…”
Section: Commentunclassified